The Impact of COVID-19: An Opportunity to Reaffirm the Central Role of Migrants’ Human Rights in Sustainable Development - Economic Commission for Latin America; the Caribbean (United Nations, 2021)
In terms of migration, the coronavirus disease (COVID-19) pandemic has come at a time already characterized by involuntary migration and growing intraregional movements, resulting in a migrant population estimated at more than 40 million. This situation has been marked by increased emigration from the Bolivarian Republic of Venezuela, a new migration route from Haiti to South America, and various vulnerabilities associated with the route that crosses Central America, Mexico and the United States. During a pandemic, the vulnerabilities that pervade the migration cycle are heightened, such as the risks of job losses; declines in paid domestic employment for women; overrepresentation of migrant workers in front-line jobs; indefinite detention; a lack of prompt access to documentation needed for health care; poor housing conditions; and stigmatization of returnees in their communities of origin, especially when returning from the United States. The pandemic poses specific migration governance challenges in the region in terms of the range of unresolved situations for migrants. These relate not only to the humanitarian, social and economic spheres that significantly affect women, but also to health and habitability issues.